Smoking and Ischemic Stroke - Uddin, Md Jalal; Mondol, Badrul Alam; Ahmed, Shahrukh; Ullah, AKM Anwar; Jabbar, MA; Mohammad, Quazi Deen (Bangladesh Journal of Neuroscience, 2009)
This case control observational study was conducted in Neurology Department of Dhaka Medical College Hospital (DMCH) to determine the relation of smoking with ischemic stroke. Fifty cases & 50 controls were selected following certain inclusion & exclusion criteria. The results of the study showed that mean age of ischemic stroke was 63.58 ± 10.22 years. Ischemic stroke was more common in male (M:F=2.57:1). Majority of the ischemic stroke came from middle class economic condition. Habit of smoking was equally present in case & control groups (54% & 52%) respectively. However duration of smoking was significantly longer (P< 0.01) in ischemic stroke patients (35.26 ± 9.97 yrs.) than the control group (24.12 ± 7.32 yrs.). The number of cigarette sticks taken per day was 15 ± 1.2 in stroke patients and 6 ± 1.5 per day in the control group with a significant difference between them (P< 0.01). Longer duration & increased number of cigarette sticks smoking were significantly associated with ischemic stroke (P< 0.01 & P< 0.01). DOI: http://dx.doi.org/10.3329/bjn.v24i1.3041 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) : 50-54